Legal personnel and the role of women in the family enterprise - Acosta Morales, María Gabriela; Santamaría Freire, Edwin Javier; Esparza Córdova, Luís Alberto (mktDESCUBRE; Vol 1 No 09 (2017): Ninth Edition - (January - June), 2017)
The legal structure of family businesses is the form of legal organization that allows administrative management and main source of conflict resolution that can exist in a family business. The study of family business and its structure focuses on the study of legal personality that creates risks for the property of the family and is a source of conflict within the organization. At the same time, it is discovered that conflicts are solved within the family having the mother as the main part of it, besides the risk of breaking of family ties is higher than the disappearance of the family business when conflicts come to courts.